Efficacy, safety and toxicity management of adjuvant abemaciclib in early stage HR+/HER2- high-risk breast cancer. Issue 8 (3rd August 2022) - Sammons, Sarah; Moore, Heather; Cushman, Jaycee; Hamilton, Erika
ABSTRACT: Introduction: The majority of the over 250, 000 new cases of invasive breast cancer diagnosed in the United States are driven by hormone receptor signaling (HR+). Since 2015, cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) have become the standard in combination with endocrine therapy (ET) for patients facing HR+ metastatic disease. Areas covered: There are now three approved agents in the HR+ metastatic setting such as abemaciclib, ribociclib, and palbociclib. Due to the almost doubling of progression-free survival (PFS) and improvement in overall survival (OS) in the metastatic setting, studies were conducted to examine the benefit of adding CDK4/6i in the adjuvant setting for those patients at high risk for recurrence. Despite negative results of PALLAS (palbociclib) in this setting, monarchE (abemaciclib) showed an improvement in invasive disease-free survival (IDFS) and distant recurrence-free survival (DRFS) at the 3-year time point for patients with high-risk tumor characteristics leading to its approval. Herein, we discuss the data, the population studied and for which abemaciclib is approved as well as safety, tolerability, and dose reductions for practical management of these patients. Expert opinion: Abemaciclib is appropriate and beneficial for those patients with high-risk, node-positive, hormonally driven, human epidermal growth factor receptor 2 negative (HER2-) breast cancer.